Microstructure and superconducting properties of Ca substituted Y(Ba1-xCax)2Cu3O7-δ ceramics prepaed by thermal treatment method - Dihom, Mustafa Mousa; Shaari, Abdul Halim; Baqiah, Hussein; Al-Hada, Naif Mohammed; Chen, Soo Kien; Azis, Rabaah Syahidah; Awang Kechik, Mohd Mustafa; Talib, Zainal Abidin; Abd Shukor, Roslan (Elsevier, 2017)
The effect of Ca substitution in Ba site of Y(Ba1−xCax)2Cu3O7−δ, (x = 0.00, 0.04, 0.08, 0.1 and 0.125), ceramics prepared by thermal treatment method was investigated. Surface morphology, structural and superconducting were studied using field emission electron microscope (FESEM), X-ray Diffraction (XRD) and four-probe method. FESEM analysis showed an increasing of samples’ grain size, homogeneity and compactness with increasing of Ca substitution. From XRD, the samples had orthorhombic crystal structure of space group Pmmm besides small amount of unknown peaks. The critical temperature (Tc R=zero) decreased from 87 K for the pure sample to 80 K for sample with x = 0.08, and it remained the same for samples with x ⩾ 0.08. Sample with x = 0.04 showed the sharpest superconducting transition (ΔTc), which could be due to good microstructure morphology and better crystallinity.